The pandan flora of Foja-Mamberamo Game Reserve and Baliem Valley, Papua-Indonesia - Ary Prihardhyanto Keim (BRIN Publishing (Penerbit BRIN), 2012)
Seven species of Pandanus and seven species of Freycinetia are observed in Kwerba and adjacent areas within the Foja-Mamberamo Game Reserve, Papua-Indonesia. Two species are proposed as new: Freycinetia kwerbaensis A.P. Keim and Pandanus korwae A.P. Keim. This recent study also acknowledges a new record for F. mariannensis and a possibly new record for F. vidalii. The rest are extension of distribution areas in mainland New Guinea. The discovery of a long searched almost mythical wild type of widely cultivated P. conoideus is also accomplished. A new species from Baliem Valley nearby Wamena in the Jayawijaya Mountains, Papua-Indonesia namely F. wamenaensis A.P. Keim is described.